IMPLEMENTASI PENERAPAN P5 DALAM PENDEKATAN CULTURALLY RESPONSIVE TEACHING DI SMKN 8 SEMARANG - Yuliana, Dimas Indra (Journal of Physical Activity and Sports (JPAS), 2024)
This study aims to determine the application of the Culturally Responsive Teaching (CRT) approach in the Pancasila student strengthening project (P5) at SMK N 8 Semarang. The CRT approach is a learning method in which all students can receive the same teaching, without distinguishing their cultural background. P5 activities are applied to develop the character profile of Pancasila school students. The study used a qualitative method with descriptive data analysis techniques. Descriptive data analysis techniques explain the facts and phenomena found in applying CRT in the P5 project. The results of this study are the application of the CRT approach in P5 activities at SMK N 8 Semarang by integrating songs, dances, and regional musical instruments in classroom learning. Students are introduced to Central Javanese culture by practising regional songs and dance every Wednesday in the P5 subject. The conclusion of this study is that students at SMK N 8 Semarang apply CRT in the P5 project by making Central Javanese culture, especially traditional dances and regional songs, into co-curricular activities that are carried out for six hours a week and integrating cultural topics.